Aishite imasu - Lamangan, Joel; Santos, Judy Ann; Santiago, Raymart; Manalo, Jay; Trillo, Dennis (Bas Film Production, 2004)
It's December 1941, and the simple folk of the quiet town of San Nicolas are unaware that war is nearly upon them. Inya (Judy Ann Santos) is lovely young lady who has just married childhood sweetheart Edilberto (Raymart Santiago) and they're excited about starting a family, Ignacio (Dennis Trillo) is Inya's best friend, a gay man who has been in love with the handsome Edilberto. The arrival of the Japanese trows the town into chaos.